A JURIDICAL REVIEW OF LEGALITY AND BURDEN OF PROOF OF WIRETAPPING EVIDENCE IN CASES OF CORRUPTION CRIMES BASED ON LEGAL REGULATIONS IN INDONESIA - Ina Heliany; Wuwuh Andayani; Edy Supriyanto (Yayasan Education and Social Center, 2022)
Amid national development efforts in various fields, people's aspirations to eradicate corruption and other irregularities are increasing. It is because, in reality, the existence of criminal acts of corruption has caused enormous state losses, which can impact the emergence of crises in various fields. The number of defendants in corruption cases acquitted by general courts or state courts was based on various reasons. One was the corruption charge against the defendant, but it proved it. The legislators were well aware of the difficulties that law enforcers may face in proving criminal acts of corruption. Thus, besides continuing to refer to the legal aspects of general proof regulated in the Criminal Procedure Code (KUHAP), legislators provided exceptions for proving corruption cases. One of them was using digital/electronic proof, such as email, telegram, wiretapping, teleconference, video conference, or CCTV footage. Based on the previous explanation, this study was aimed at elaborating on the legality of wiretapping at the stage of the investigation process in corruption cases and the evidentiary value of wiretapping communication/telephone devices based on the provisions of Article 183 of the Criminal Procedure Code to optimize the disclosure of corruption in Indonesia. The research method used was a qualitative method through a normative juridical method, namely the method used by mastering the law for a particular problem and how to implement or apply these legal regulations. From the results, the research found that in the Criminal Procedure Code (KUHAP), there was also an article that regulates wiretapping, namely Article 7 paragraph (1) j states that: